2021
DOI: 10.3389/fonc.2021.755378
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study on the Application of Enhanced Recovery After Surgery Measures to Promote Postoperative Rehabilitation in 50 Patients With Brain Tumor Undergoing Craniotomy

Abstract: ObjectiveTo investigate whether enhanced recovery after surgery (ERAS) can promote rehabilitation of patients after neurosurgical craniotomy.MethodsThe clinical data of 100 patients with brain tumor undergoing craniotomy in the Department of Neurosurgery, Xiangya Hospital, Central South University, from January 2018 to August 2020 were collected, including 50 patients in the ERAS group and 50 patients in the control group. t-Test, Wilcoxon’s rank sum test, and chi-square analysis were used to compare the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Movement and early mobilization following brain tumor surgery have proven to be effective in facilitating patients' recovery. However, patients may exhibit reluctance or encounter difficulties when it comes to movement, primarily due to the pain they experience, the presence of various care equipment attached to their bodies, and the fear of potential damage to the surgical site (Wang et al, 2019;Feng et al, 2021). Patients who have undergone spinal surgery (Archer K et al, 2014), as well as those with lumbar disc herniation (Svensson et al, 2011) and lumbar spinal surgery (Kemani et al., 2020), often experience fear of movement, which subsequently leads to reduced participation in physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Movement and early mobilization following brain tumor surgery have proven to be effective in facilitating patients' recovery. However, patients may exhibit reluctance or encounter difficulties when it comes to movement, primarily due to the pain they experience, the presence of various care equipment attached to their bodies, and the fear of potential damage to the surgical site (Wang et al, 2019;Feng et al, 2021). Patients who have undergone spinal surgery (Archer K et al, 2014), as well as those with lumbar disc herniation (Svensson et al, 2011) and lumbar spinal surgery (Kemani et al., 2020), often experience fear of movement, which subsequently leads to reduced participation in physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our current results confirmed this measure to be safe and effective for glioma patients. In addition, early mobilization can reduce the risk of pulmonary complications and DVT, as well as improve cardiopulmonary function ( 16 , 17 ). In our case series, patients in the ERAS group were encouraged to ambulate on the first day after the operation, which was associated with shorter LOS and better rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was reported in 7 studies, 9,[36][37][38][40][41][42] and a pooled analysis of these studies revealed no significant differences in mortality between the ERP and non-ERP groups, with 4 deaths reported in each group. The incidence of the other complications was also not significantly different between the ERP and non-ERP groups (Table 3).…”
Section: Mortality and Complicationsmentioning
confidence: 96%
“…All records from the citation search were excluded after fulltext screening of individual ERP interventions. [27][28][29][30][31][32][33][34][35] Subsequently, 8 records, 9,36-42 including 3 RCTs, 9,36,37 3 prospective studies, 39,40,42 and 2 retrospective studies 38,41 published between 2019 and 2022, were included (Table 1).…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation